Epidemiological Study of Bell's Palsy in patients From Western Nepal - Koirala, Krishna Prasad (Eastern Green Neurosurgery, 2020)
Background: Bell's palsy is defined as idiopathic, sudden onset, unilateral lower motor neuron facial paralysis. The etiology of Bell's palsy is unclear. It affects all age ranges with complete recovery in most cases. However, few patients are left with a considerable permanent functional deficit. The disease has variable progression ranging from few hours to days. Diagnosis is usually made when a patient presents with sudden onset unilateral lower motor neuron facial paralysis without an obvious cause. Different medical therapies such as steroids, antivirals, physiotherapy, acupuncture, etc. have been used to enhance the recovery of Bell's palsy. This study aims to find out the common age of presentation of people with Bell's palsy, and also to report their outcome with the use of steroids.Materials and methods: This study is a prospective observational study carried out in the department of ENT and Head and neck surgery at Manipal College of Medical Sciences, Pokhara, Nepal. Patients of all ages and both sex with the diagnosis of Bell's palsy meeting the inclusion criteria were studied from 1st Jan 2015 to 31st Dec 2018. Data were taken and analyzed with the help of SPSS software and results were published.Results: Out of 45 patients of Bell's palsy enrolled in the study, females outnumbered the males. Bell's palsy was more commonly seen in young adults There was a significant short-term improvement in Bell's palsy with the use of steroids (p=0.00001). There was no difference in early recovery after Bell's palsy regardless of the time of presentation within a week or age of the patient at presentation.Conclusion: Bell's palsy is more common in young adults. Steroids have a definite role in the short-term improvement of facial nerve function. People presenting within a week of facial nerve palsy can be treated with steroids. People of all ages can equally improve with steroid treatment.